A picosecond laser-based ion source for injection into a high capacity EBIS in both accumulation and single pulsed modes. Issue 1 (1st April 2022) - Kondrashev, S.; Beebe, E; Kanesue, T.; Okamura, M.; Scott, R.
Abstract: Ps-lasers have advantages for generation of low charge state ions compared to ns-lasers because the influence of heat conductivity on a solid target is negligible in the case of ps-laser ablation for laser pulse durations shorter than 10 ps. By using a laser with high rep-rate, it is possible to produce quasi continuous 1+ ion beams for periods up to tens of milliseconds, making it possible to take advantage of the ability of the EBIS to trap 1+ ions in accumulation injection mode. We studied the properties of Al, Ti, Cu, Nb, and Ta plasmas generated by a ps-laser with 1.27 mJ energy within an 8 ps pulse to investigate feasibility and specify parameters of a laser ion source for RHIC EBIS using accumulation injection mode. It is shown that a both accumulation and single pulsed injection modes are accessible with a single ion source geometry and single injection line, providing the most attractive option for an ion source for external injection into RHIC EBIS trap based on a ps-laser.